Red Faction Armageddon. - Burt, Andy.
Volition's upcoming destructive sandbox adventure adds a new mission structure and ups the demolition levels set by 2009's Red Faction: Guerilla.
Keywords: Armageddon; Video games; First-person shooter video game; Geo-Mod physics engine; Red Faction (Game).